2017
DOI: 10.1175/bams-d-14-00284.1
|View full text |Cite
|
Sign up to set email alerts
|

The Tropical Air–Sea Propagation Study (TAPS)

Abstract: The purpose of the Tropical Air–Sea Propagation Study (TAPS), which was conducted during November–December 2013, was to gather coordinated atmospheric and radio frequency (RF) data, offshore of northeastern Australia, in order to address the question of how well radio wave propagation can be predicted in a clear-air, tropical, littoral maritime environment. Spatiotemporal variations in vertical gradients of the conserved thermodynamic variables found in surface layers, mixing layers, and entrainment layers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The results of the Tropical Air-Sea Propagation Study and others show typical duct heights of 2-30 m (Ivanov et al, 2009;Kulessa et al, 2017;Wang et al, 2009) with long-term averages of 8 m in the northern latitudes and 30 m in the tropics (Hitney et al, 1985). The ranges of duct heights and M deficits associated with the trial parameters are consistent with the ranges observed in these studies.…”
Section: Numerical Experimentssupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the Tropical Air-Sea Propagation Study and others show typical duct heights of 2-30 m (Ivanov et al, 2009;Kulessa et al, 2017;Wang et al, 2009) with long-term averages of 8 m in the northern latitudes and 30 m in the tropics (Hitney et al, 1985). The ranges of duct heights and M deficits associated with the trial parameters are consistent with the ranges observed in these studies.…”
Section: Numerical Experimentssupporting
confidence: 83%
“…The trial refractivity parameters used in this study ( c 0 , z d , and m 1 ; Table ) were selected based on the Saeger et al () study evaluating simplified evaporation duct models for inversion problems, as well as from evaluation of atmospheric data from the Tropical Air‐Sea Propagation Study (Kulessa et al, ). The results of the Tropical Air‐Sea Propagation Study and others show typical duct heights of 2–30 m (Ivanov et al, ; Kulessa et al, ; Wang et al, ) with long‐term averages of 8 m in the northern latitudes and 30 m in the tropics (Hitney et al, ). The ranges of duct heights and M deficits associated with the trial parameters are consistent with the ranges observed in these studies.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous conditions can be classified into superrefraction, subrefraction, or ducting (trapping). Superrefraction, which is associated to subsidence, advection, or surface heating occurs when the atmospheric thermodynamic conditions cause the radio signals to refract much more than usual (Gunashekar, 2006; Kulessa et al, 2017). Subrefraction is a situation when the radio beam refracts less than usual, diminishing radio horizon, and its effects are less evident and occur less frequently, but it is relevant when correcting topographic beam blockage in radar rainfall estimation in complex terrain (Bech et al, 2007; Magaldi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Above mentioned models and tools are accompanied with increasing improvement in lower troposphere refractivity and sea state estimation/analysis in different area of the world and sophisticated refractive environmental modeling including inversion techniques [15][16][17][18][19]. In [18] are summarized the last 20 years field campaigns for data collection whereas [19] reviews previous work in estimating the atmospheric conditions from electromagnetic measurements which assures real-time tracking of atmospheric parameters.…”
Section: Introductionmentioning
confidence: 99%